Spin-state ordering in hydroxo-bridged Diiron(III)bisporphyrin complexes - Sainna, Mala A.; Sil, Debangsu; Sahoo, Dipankar; Martin, Bodo; Rath, Sankar Prasad; Comba, Peter; Visser, Sam P. de (Inorganic chemistry, 2015)
We report the synthesis, structure, and spectroscopic characterization of 1,2-bis[μ-hydroxo iron(III) 5-(2,3,7,8,12,13,17,18-octaethylporphyrinyl)]ethane with PF6- and SbF6- counteranions. The two iron centers are nonequivalent with admixed intermediate spin state (S = 3/2 with a minor contribution of S = 5/2) on each metal both in the solid and in solution. The molecules are compared with previously known μ-hydroxo complexes with other counterions, such as I3-, BF4-, and ClO4-, which demonstrates that the nature of the counterion can affect the spin-state ordering dramatically. To understand how the spin-state ordering is affected by external perturbations, we also have done a comprehensive computational study. The calculations show that subtle environmental perturbations affect the spin-state ordering and relative energies and are likely to be the root cause of the variation in spin-state ordering observed experimentally.
Gesehen am 09.07.2020